Ammonia predicts poor outcomes in patients with hepatitis B virus‐related acute‐on‐chronic liver failure. Issue 12 (11th September 2020) - Zhang, JinFei; Liu, XiaoLu; Ye, Bo; Chen, Hui
Abstract: Background: Hepatic encephalopathy (HE) is a common feature of acute liver failure and has been reported to be associated with poor outcomes. Ammonia is thought to be central to the pathogenesis of HE, but its role in hepatitis B virus‐related acute‐on‐chronic liver failure (HBV‐ACLF) is unclear. The present study aimed to assess the prognostic role of ammonia level for patients with HBV‐ACLF. Methods: We retrospectively recruited 127 patients diagnosed with HBV‐ACLF for the present study. Results: Ammonia levels at the time of admission were higher among non‐surviving participants than in survivors. Increased ammonia level was found to be associated with severe liver disease and was identified as an independent predictor for mortality in patients with HBV‐ACLF. Conclusions: Our results suggest that high ammonia level at admission is an independent factor for predicting short‐term mortality in patients with HBV‐ACLF. Therefore, ammonia levels may represent a therapeutic target for this condition. Abstract : Receiver operating characteristic curves indicating the relative efficiencies of Chinese Group on the Study of Severe Hepatitis B Acute‐on‐Chronic Liver Failure score, ammonia level and the combination of both for predicting 28‐day mortality in patients with hepatitis B virus‐related acute‐on‐chronic liver failure.